2015
DOI: 10.1007/s40710-015-0072-8
|View full text |Cite
|
Sign up to set email alerts
|

Water Budget Assessment within a Typical Semiarid Watershed in the Eastern Mediterranean

Abstract: Adequate evaluation of blue water fluxes in arid and semiarid areas is crucial for operational purposes such as evaluation of rain-fed agriculture, grazing potentials and for designing and construction of water dams. Evapotranspiration, runoff and deep recharge in such catchments are poorly understood due to the lack of meteorological and/or hydrological measurements. Modeling using proper parameterizations would probably be a viable alternative to gauge such resources. The present paper examines the water bud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…Modelling of runoff from snowmelt in regions where the snowpack is marginal has frequently involved the use of temperature-index models (TIMs; Bormann et al, 2014;Dunn & Colohan, 1999;Oroud, 2015;Samuels, Rimmer, Hartmann, Krichak, & Alpert, 2010;Schreider, Whetton, Jakeman, & Pittock, 1997). These are based on data that are widely available (Hock, 2003) and may be utilised without knowledge of the local energy balance.…”
Section: Introductionmentioning
confidence: 99%
“…Modelling of runoff from snowmelt in regions where the snowpack is marginal has frequently involved the use of temperature-index models (TIMs; Bormann et al, 2014;Dunn & Colohan, 1999;Oroud, 2015;Samuels, Rimmer, Hartmann, Krichak, & Alpert, 2010;Schreider, Whetton, Jakeman, & Pittock, 1997). These are based on data that are widely available (Hock, 2003) and may be utilised without knowledge of the local energy balance.…”
Section: Introductionmentioning
confidence: 99%
“…A small change in T a appears to have a minor influence on β . It should be indicated that in this sensitivity analysis, atmospheric relative humidity is assumed constant, and thus, the actual vapour pressure ( e a ) of air is allowed to respond to air temperature because ambient water vapour pressure synchronizes closely with air temperature even in arid climates (e.g., Allen et al, ; Oroud, ). If the ambient vapour pressure was kept constant following the temperature departure, then the effect of air temperature increase would have more effect on brine activity (not shown in Figure ).…”
Section: Evaporation Constraintmentioning
confidence: 99%
“…As typical for Mediterranean climate watersheds, the pollutant loads are predominantly contributed by a limited number of intense flood events, whereas the contribution of all of the other events is negligible. While somewhat limited, a number of studies have applied catchment level models to Mediterranean watersheds (Gikas et al 2006;Pisinaras et al 2010;Licciardello et al 2007;Bisantino et al 2013;Chamoglou et al 2014;Oroud 2015). These studies indicated that the model predictions were suitable for runoff and satisfactory for the sediment and nutrient loads.…”
Section: Modeling Water Quality At the Watershed Scalementioning
confidence: 99%